(untitled) (Research, Society and Development, 2021)
Introduction: sexuality, in contemporary times, is still understood by many as a synonym for sex. However, this concept goes beyond the sexual act itself, being, according to the German psychoanalyst Sigmund Freud, something similar to an instinct, to a vital force that is responsible for the self-perception of oneself and others, thus consisting of something inherent to human nature. Objective: to analyze the relevant aspects of sexuality in old age. Methodology: this is an integrative literature review, with articles selected from the following databases: National Library of Medicine (PubMed MEDLINE), EbscoHost, Google Scholar, Scientific Electronic Library Online (SCIELO) and Virtual Health Library (VHL). Results: it was found that the most relevant aspects for the discussion of sexuality in old age are morphophysiological changes, the cultural positioning of today’s society, Sexually Transmitted Infections (STI’s), gender identities and roles. In this regard, it is important to emphasize that biological changes, both in females and males, for example, cause hormonal, structural and functional changes in the body that incur in disturbances in wills related to sexual practice and the pleasure achieved by them. In this context, loss of lubrication and elasticity in women and less firm erections and erectile dysfunction in men are the biological elements that interfere more clearly in the sexual life of the elderly, whether causing pain (dyspauremia) or making orgasm difficult. Gender issues are also relevant in the experience of sexuality among the elderly, because, nowadays, the need for heteronormative gender roles to be represented is still predominant in the collective consciousness, directly preventing it; through aggression, and indirectly; through social pressures, older individuals belonging to the LGBTQIA+ community express themselves and experience their wishes. Conclusion: intrinsic factors are related to natural aging processes and extrinsic factors are correlated with sociocultural aspects. Therefore, the necessary interventions so that the sexuality of the elderly is experienced in a satisfactory way involve both medical issues that can help in the alleviation of biological changes and the prevention of STI’S, as well as socio-educational issues aimed at treating the sexuality of the elderly person naturally.